Progressive landslide analysis : Applications of a Finite Difference Method by Dr. Stig Bernander Case Study of the North Spur at Muskrat Falls, Labrador, Canada - Dury, Robin (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2017)
An easy-to-use spreadsheet version of a finite difference method for progressive landslide analysis has been developed. The finite difference method was originally developed by Dr. Stig Bernander, earlier adjunct professor at Luleå University of Technology and head of the Design Department of Skanska AB in Gothenburg, Sweden. The so called Muskrat Falls Project consists in the ongoing construction of a hydroelectric power plant in Churchill River Valley, Labrador, Canada. The site hosting the project includes a land ridge which is supposed to be used as a natural dam and thus be submitted to important water pressures. Yet, previous landslides in the area have shown that a stability analysis is worth to be carried out in order to ensure the safety of the facility. Until now, investigations have only been carried out using the traditional limit equilibrium method and related elastic-plastic theory. For the sake of simplicity, this approach does not take into account deformations outside and inside the sliding body. However, because of the soil features in Churchill River Valley and particularly its ‘deformation softening’ behavior, there is increasing evidence that the conventional analysis is not relevant in this situation. Further, when analyzing the total stability of the ridge, only a horizontal failure surface has been used and not an inclined one, which is very optimistic and rather unrealistic. In order to provide a more reliable study, a progressive failure analysis has been performed according to the finite difference method of Dr. Stig Bernander. The development of a spreadsheet adapted to this particular problem has allowed getting quickly and easily numerical results for several cases of study and assumptions. For assumed material properties and geometries of failure, the critical load-carrying capacity is below 1000 kN/m whereas a rise of the water level with 21 m will give an increased load of Nq = 2420 kN/m. This is more than twice of the what the ridge may stand with the assumed properties. The ...